Cholesterol-lowering effect of mevinolin, an inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme a reductase, in healthy volunteers. - Tobert, J A (1982)
Mevinolin reduces cholesterol synthesis by inhibiting 3-hydroxy-3-methylglutaryl-coenzyme A reductase. The safety and effectiveness of this agent was evaluated in a double-blind, placebo-controlled study in 59 healthy men (serum cholesterol 3.88--7.76 mmol/liter) in five centers. Subjects maintained their usual diet and activities. Doses of 6.25, 12.5, 25, or 50 mg twice daily for 4 wk produced mean reductions of total serum cholesterol fo 23--27% [vs. placebo (4%), P less than 0.01]. Mean low density lipoprotein cholesterol fell 35--45%, while high density lipoprotein and very low density lipoprotein cholesterol, and triglycerides were not significantly affected. Mean apolipoprotein B fell 27--34%. 50 mg was not significantly more effective than 6.25 mg. Mevinolin was generally well tolerated, and no serious clinical or laboratory abnormalities occurred. One subject (12.5 mg) was withdrawn because of abdominal pain and diarrhea. These results suggest that if long-term safety can be demonstrated, inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A reductase are likely to prove useful in the treatment of hypercholesterolemia.